Agile Foundations LiveLessons - Layton, Mark (Addison-Wesley Professional, 2016)
More than 4 hours of live training to teach you what you need to know about Agile and Scrum Foundations. Overview Learn the basics needed to get started with Agile and Scrum! Description Agile Foundations Complete Video Course will teach you what you need to know to fully understand the concepts of Agile and Scrum. Through screencasts and live training, you will explore the fundamentals of Agile techniques, how Scrum leverages Agile principles to improve project performance, the specifics of the Scrum framework, how to experience amazing benefits with Scrum today, and real-world situations, like transitioning and common pitfalls. Even though the concept of Scrum itself is easy to explain, the application is often difficult. Real-world success stories across various industries will help you see how scrum fits each unique situation. Known globally as Mr. Agile and the author of Agile Project Management for Dummies and Scrum for Dummies ' Mark Layton will comprehensively establish a foundation in the 3 roles, 3 artifacts, and 5 events of Scrum. With examples from Fortune 1000 companies and other common practice tips, the course will apply to those in the IT business, manufacturing, construction, healthcare, education, and even to stay-at-home moms. Introduced recommendations, metrics, and resources will prove useful information to continue your journey in implementing Agile techniques, with an emphasis on the Scrum framework. This title includes: More than 4 hours of complete video training Video exercises so you can practice your knowledge Quizzes to help you learn and retain concepts Hands-on exercises to help you retain key knowledge Topics include: Basics of Scrum Agile Manifesto and Principles Strategic Direction with vision statements and product roadmaps Scrum Roles, artifacts, and events Estimating and Setting Appropriate Expectations Scrum in Action Inspect and Adapt Skill Level Beginning What You Will Learn Agile and Scrum fundamentals Agile manifesto and principles Strategic directions Scrum roles Estimating and Setting Appropriate Expectations Scrum in Action Inspect and Adapt Who Should Take This Course The primary target market for this course is someone involved with a project that is looking to improve that project'Äôs performance through earlier visibility. Secondarily, anyone looking to improve their project management expertise through scrum master certification. While the most popular market is the in software industry, ther...
Not recommended for use on the libraries' public computers